Effects of repeated hemolymph sampling from adductor muscles of relaxed Pacific oysters (Magallana gigas) - Jingwei Song; Alexander A. Langley; Michael A. Banks; Bernarda Calla (PLoS ONE, 2025)
Hemolymph is vital for bivalves, contributing to their innate immune system, nutrient transport, waste elimination, and hormone regulation. Yet, traditional sampling methods are often invasive or fatal to the organisms. In this study, we evaluated the effects of repeated, non-lethal hemolymph sampling on adult Pacific oysters (Magallana gigas). Five- year-old oysters were relaxed with magnesium sulphate, and hemolymph was extracted from half of the individuals, while the other half with relaxation served as controls. Sampling took place during gonad maturation in two groups: one laboratory conditioned (approximately three months in indoor tanks with controlled environment), and one naturally conditioned (approximately seven months at the bay in Yaquina Bay, Oregon, USA). Total mortalities ranged from 10% in the laboratory groups (after four samplings) and 22% (after seven samplings) in the natural groups; most of the mortalities took place after the last sampling. Sex ratio was similar between the sampled (66%) and control groups (63%) in the laboratory setting. In the natural setting, the final sex ratio was male biased in the group that was repeatedly sampled for hemolymph (58%) compared to the non-sampled controls (28%). Our findings highlight that repeated hemolymph sampling can be performed with minimal mortality, allowing non-lethal monitoring of hemolymph physiology over time.